Design Of Android Base School Information Media Application Case Study Of Qomariah Educational Institution - Saleh, Muhammad Prakarsa Al Qadr; Ipantri, Indra (Universitas Trilogi, 2023)
Currently the world of technology and information is developing very quickly, including school information systems. The school information system is one of the information media that can be accessed by all elements of the school including teachers and students so that they can relate to each other in terms of teaching and learning activities and information that can be quickly disseminated to all students, so that students do not need to come to school. in this technological era from young to old all use smartphones to facilitate communication but PKBM Qomariah does not yet have the right information media. So an Android-based school information system application was made using Android studio. Android applications make it easier for teachers and students because they can be accessed on various smartphones. All teachers and students mostly have smartphones. With this application, teachers and students can get information from schools easily. The research method used is descriptive method by conducting observations, literature studies, and interviews. While the method used in making software is waterfall which consists of several stages, namely requirements definition, system and software design, implementation and unit testing, system integration and testing, Operation and Maintenance.